(untitled) (Research, Society and Development, 2022)
Chorioamnionitis (CA) is an acute inflammation of the placenta, chorion, and amnion, and is a common cause of adverse maternal and fetal complications whose etiology cannot always be identified. It is characterized by maternal fever, maternal and fetal tachycardia, maternal leukocytosis, and a fetid odor of the amniotic fluid. When associated with ismo-cervical incompetence it brings risk of abortion. Given the above, this study aims to report the experience of nursing students in the nursing care in a case of chorioamnionitis and isthmus cervical incompetence in hospital practice. This is a descriptive study, experience report type, developed in the months of October/November 2019, by six students and a field preceptor, in a maternity hospital in the sector of rooming-in, during internship practice located in the urban area in a city in the metropolitan region of Cariri Ceará. A search was conducted in the journal portal in the Scielo and Lilacs databases, to support a better understanding of the investigated phenomenon. The data analysis occurred through the steps of the nursing process, discussion of the complete clinical case obtained during data collection. The experience in the assistance to the case of subsidized the knowledge about the presented disease and an opportunity to learn the assistance aligning the theory from the practice during the care to the high-risk pregnancy.